The Condition of Religious Modernism among the Youth in Yazd - Hasan Zadedehghan; Mohammad Hadi Yarahmadi; Esmat Salehi (جامعه شناسی کاربردی, 2014)
Introduction The term âmodernismâ which renaissance is used as its Persian equivalence was applied in 1863 first by Charles Baudelaire in the meaning of âdestroying stereotypical formsâ that prevent from changing thoughts and customs. Modernism in comparison with rehabilitation that is an objective process, is mostly a subjective process because it is a kind of ideology, a kind of thought that tries to displace modern instead of old because it thinks modern is better than old (Sorush 1999 : 52). âCafiyar and Vensono,â in their definition of modernism, consider individualism, subjectivism and conventionality, and customization as main elements of modern society (Tapia 2000: 107). Modernism in religion is a process that is joined with innovation and rehabilitation, detached from references such as religion and custom, and displacing material rationalism instead of divine believes in organizing current life and relying on science and technology as motor power of development. Giddens believes that confrontation with past customs is in the nature of modernism (Ghasemi et al, 2010). Although modernism detaches them, dimensions of cultural modernism include three elements including criticism, customizing believes and scientism (Ghasemi et al, 2010). Some scholars such as Shojaeezand (2006) believe that coexistence of these two items is possible if they fall short in favor of the other. In religious modernism discussion, we can observe several groups in society: religious traditionalists, who insist on their traditional believes and do not accept any criticism and idea in religious issues. But in our society, we seem to have modernists who both accept traditional laws of religion and scientism and critical bases in religion. This group accept religion and its bases by a new view. This is a circumstance that our modern society accepts. Of course it can be said that this is the same scientism and religious rationalism that our religious bases point to it again and again. And this group can be also placed in traditionalists group because science, experience and rationalism are original bases of modernism and display other aspects of its modernism by appearing rationalism and we trap into western modernism. Other group include extreme modernists that want to determine all bases of religion and tradition by rules of modernism, and sometimes lead to secularism. So modernism is not free of difficulty in the area of religion and as some researchers (e.g. Salehi 2010) showed, it is joined with social disorders. Materials and Methods This is a survey study, performed as cross-sectional. The research statistical population include 15-40 year old citizens of Yazd. Sample size was estimated to be 384 individuals by Cochran formula and multi-step cluster sampling method was used for selecting subjects. For collecting data, a standard questionnaire about religious modernism was used. In order to determine the validity of religious modernism, content validity was used, which means that the validity and value of the scale was confirmed by experts. For measuring reliability of the scale, Cronbach's Alpha coefficient was used. Finally, the data was analyzed using SPSS software. Discussion and conclusion As the results show, the level of religious modernism in each of its five dimensions, is low among the youth of Yazd. Experimentalism and scientism are more popular in religious bases among the youth and elements such as humanism, and individualism are low in religion. Also religious modernism correlate with variables such as age, gender, education, employment type and well-being of the family. In particular, the younger the subjects, and higher their level of education, and higher their rank in job, the higher their tendency toward religious modernism as well. Modernism in religion area is of double significance in our society, especially in Yazd. If religious bases are reconciled by principles such as rationalism and scientism, an ideal situation may appear and we may not experience social disorders anymore, because Islam wants people to accept religious principles thoughtfully and their acceptance is not in conflict with some principles of modernism.